THE CONVERTER FORMS OF A VOLTAGE TO THE SYSTEM POWER SUPPLY CONTACT SYSTEM AC - Panasenko, N. V.; Honcharov, Ju. P.; Zamarujev, V. V.; Kryvoshejev, S. Yu.; Ivanov, O. Je.; Morozov, P. P.; Sichenko, V. H. (Science and Transport Progress, 2009)
The structures of sine voltage to quasi-meander shape voltage converters, which allow increasing up to two times the traffic carrying capacity of the feeder mains, are considered.